Pengaruh Intellectual Capital, Corporate Social Responsibility Disclosure pada Kinerja Pasar (Studi Perusahaan Perbankan Di BEI) - Suastyani, Kadek Novia; Ary Wirajaya, I Gede (E-Jurnal Akuntansi; Vol 26 No 1 (2019)DO - 10.24843/EJA.2019.v26.i01.p19, 2019)
This study purpose to determine the effect of intellectual capital, corporate social responsibility disclosure on market performance. This research was conducted on banking companies listed on the Indonesia Stock Exchange in 2014-2016, namely as many as 43 companies. Samples were taken using non-probability sampling techniques with purposive sampling method. Obtained 23 companies with 69 total observations. The data analysis technique used is multiple linear regression analysis. The results of the analysis prove that companies that are able to process value added well will affect market performance. This study also found that the more items disclosure of CSR disclosure disclosed by the company will improve market performance. Keywords : intellectual capital, corporate social responsibility disclosure, market performance